Automatic Fuzzy Logic–Based Nutrient Film Technique Hydroponic System with IoT Integration - Muhammad Akmal; Ida Laila; Arifin Arifin (Newinera Publisher, 2026)
This study addresses the need for efficient crop cultivation solutions, particularly in urban areas, by developing an automatic Nutrient Film Technique (NFT) hydroponic system integrated with the Internet of Things (IoT). Traditional hydroponic systems often require intensive monitoring and can be rigid in adapting to changing conditions, especially when using binary logic for control. The proposed system utilizes fuzzy logic as its core calculation method to manage uncertainty in decision-making, allowing for more flexible control than classical binary logic. It incorporates pH, Total Dissolved Solids (TDS), temperature, and water level sensors, connected to an Arduino Nano and ESP32 microcontroller. Data is stored and communicated in real-time via Firebase, and the system is controlled through an Android application developed with MIT App Inventor. This design aims to enhance automation, improve system control, and enable more efficient management of hydroponic operations.